Hypothalamic Neuroendocrine Functions in Rats with Dihydrotestosterone-Induced Polycystic Ovary Syndrome: Effects of Low-Frequency Electro-Acupuncture - Feng, Yi; Johansson, Julia; Shao, Ruijin; Mannerås, Louise; Fernandez-Rodriguez, Julia; Billig, Håkan; Stener-Victorin, Elisabet (PLoS ONE, 2009)
Adult female rats continuously exposed to androgens from prepuberty have reproductive and metabolic features of polycystic ovary syndrome (PCOS). We investigated whether such exposure adversely affects estrous cyclicity and the expression and distribution of gonadotropin-releasing hormone (GnRH), GnRH receptors, and corticotrophin-releasing hormone (CRH) in the hypothalamus and whether the effects are mediated by the androgen receptor (AR). We also assessed the effect of low-frequency electro-acupuncture (EA) on those variables. At 21 days of age, rats were randomly divided into three groups (control, PCOS, and PCOS EA; n = 12/group) and implanted subcutaneously with 90-day continuous-release pellets containing vehicle or 5alpha-dihydrostestosterone (DHT). From age 70 days, PCOS EA rats received 2-Hz EA (evoking muscle twitches) five times/week for 4-5 weeks. Hypothalamic protein expression was measured by immunohistochemistry and western blot. DHT-treated rats were acyclic, but controls had regular estrous cycles. In PCOS rats, hypothalamic medial preoptic AR protein expression and the number of AR- and GnRH-immunoreactive cells were increased, but CRH was not affected; however, GnRH receptor expression was decreased in both the pituitary and hypothalamus. Low-frequency EA restored estrous cyclicity within 1 week and reduced the elevated hypothalamic GnRH and AR expression levels. EA did not affect GnRH receptor or CRH expression. Interestingly, nuclear AR co-localized with GnRH in the hypothalamus. Thus, rats with DHT-induced PCOS have disrupted estrous cyclicity and an increased number of hypothalamic cells expressing GnRH, most likely mediated by AR activation. Repeated low-frequency EA normalized estrous cyclicity and restored GnRH and AR protein expression. These results may help explain the beneficial neuroendocrine effects of low-frequency EA in women with PCOS.